Kukis-MNL: A feasibility study about Filipino dessert flavors on taro-flour based cookies - Castillones, Finella M.; De Leon, Josiah Cedric J.; Lamasan, Feane Joven C.; Leonardo, Remar G.; Odsinada, Clarence Ivar D.; Reyes, Justine Monica T.; Tirol, Throylan Dave C.; Villaruel, Sandra D. 4 0 16; 5
EXECUTIVE SUMMARY: Cookies are a type of small, flattened cake the usually has a crispier consistency than cake, which is baked in batches in a flat pan. Many types of basic cookie dough can be prepared, and a variety of ingredients can be added to the basic dough such as chocolate chips, dried fruit, or nuts. The cookies that will be baked are made with taro floour which will be incorporated with Filipino dessert flavors as Dulce de Leche, Ube, Yema Mango, Pastillas, and Buko. Each cookie will weigh 60 grams. Each flavor is a wordplay between local literary characters, words, and the Filipino-desserts flavors: Maki-BUKO, wag matakot is a cookie that is based on rallying people from Manila that usually says the word Maki-Baka, 'wag matakot and the word Buko. It is a coconut flavored cookie, a cookie dough mixed with coconut jam that is baked to have a tropical, creamy, nutty, and slightly sweet flavors. This Crisostomo UBE-rra is based on a literary character named Crisostomo Ibarra from the national hero's literary novel called Noli Me Tangere and the word Ube. It is an Ube flavored cookie, a cookie dough mixed with Purple Yam Jam that is baked to have sweet, nutty and vanilla-loke taste. Derived from the demure Noli Me Tangere Character Maria Clara and Mangga. The cookie Maria MANGGA is a cookie dough mixture in cooperated with mango, resulting in a sweet tropical fruity and chewy texture yet has a good crunch from the cookie itself. Juan YEMA is a word play between the well-known Filipino boy name Juan and the word Yema which is a sweet custard candy that is wrapped in thin cellophane wrappers. The cookie is a combination of cookie dough with a Yema spread on the center, resulting in a creamy sweet, sugary flavored. Dulce de LECHE is a confection that is made with caramelized milk that is cooked on low heat that is being cooked for several hours and Leche Flan which is a pudding that is made with yolk, milk, and sugar. The Cookie is a mixture of baked cookies with a leche flan pudding and with a caramel drizzle that shows a very sweet yet creamy texturized cookie flavor. PASTILLAS Muralla is a word play between the Spanish word Muralla which means walls and the dessert called Pastillas which is a milk candy, it is a cookie mixed up with pastillas spread that brought up the flavors of sweet, milky, and creamy, and the cookie resembling to a rough wall with a powdery finish that shows to a resemblance to a Pastillas itself. Kukis-MNL offers Bottled Iced Coffee by Brew Basics on the menu which can be brought separately with or without cookies, there is a total of six flavors: Salted caramel, Hazelnut, White mocha, Long Black, White, and lastly Mocha. KukiS-MNL can also be bought on a Kraft tub with three (3) sizes from 8 oz, 12 oz, and 16 oz which ranges customers also have an option to choose varieties of flavors depending on the size of the tub they will going to use for 8 oz it will be three (3) flavors, for 12 oz will be four (4) flavors and lastly, for 16 oz it will for all six (6) flavors. KADA-Bundles is a promo bundle combination of bulk orders of cookies tubs and bottled iced coffee, Kukis-MNL offers 3 KADA-Bundles selection of flavors of the cookies and coffee can be done by either the customer or the staff. The business Kukis-MNL was established to create a taro flour-based cookie with Filipino-flavored dessert for a pastry through substituting taro flour by sacrificing not to use wheat flour. The business also aims to impact consumers through its unique name, in which they can remember the brand, tagline, and product itself.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2